Henry Melchior Muhlenberg and the American Revolution - Tappert, Theodore G. (Church history, 1942)
The growing tension between the American colonies and England in the decade preceding the Revolution confronted conscientious colonists with the necessity of making a difficult decision. Pressure to reach a decision was immeasurably increased when friction developed into war. It was relatively easy for some colonists to make up their minds as to whether or not they should remain loyal to the British crown. Those who were called Whigs or Tories recognized no serious problem; political ideals and allegiances, considerations of self-interest, and long standing prejudices united in various ways to make them zealous patriots or ardent loyalists. But these extremists were in a decided minority at the beginning of the Revolution. The majority of the colonists occupied ground somewhere in between; they were conservatives who hoped for a compromise solution of the differences between England and America, or wavered in distrustful indecision, or had no conviction whatsoever in the matter. It would be unjust lightly to prejudge their motives as of necessity either nobler or baser than those of the patriots and loyalists. Particularly unhappy was the lot of those who were unable to reach a conscientious decision either for or against the struggle for independence.